2022
DOI: 10.3390/en15041322
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Decentralized Hydrogen Systems: Lessons Learned and Challenges from German Regions

Abstract: Green hydrogen produced by power-to-gas will play a major role in the defossilization of the energy system as it offers both carbon-neutral chemical energy and the chance to provide flexibility. This paper provides an extensive analysis of hydrogen production in decentralized energy systems, as well as possible operation modes (H2 generation or system flexibility). Modelling was realized for municipalities—the lowest administrative unit in Germany, thus providing high spatial resolution—in the linear optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Hydrogen storage is a promising option suitable for long-term seasonal storage of excess power generated by variable renewable energy sources, as explained in [19]. The surplus power is converted to hydrogen as an energy carrier, which can be further converted to methane, methanol or other synthetic fuels.…”
Section: Related Work and Problem Statementmentioning
confidence: 99%
“…Hydrogen storage is a promising option suitable for long-term seasonal storage of excess power generated by variable renewable energy sources, as explained in [19]. The surplus power is converted to hydrogen as an energy carrier, which can be further converted to methane, methanol or other synthetic fuels.…”
Section: Related Work and Problem Statementmentioning
confidence: 99%
“…Nevertheless, using Germany as an example, many business models may not be viable under current market conditions. Jarosch et al [108] found that the price of hydrogen needs to be sufficiently high and changes in electricity price components, such as more flexible grid-usage fees, must be realized. Other forms of long-term energy storage may be taken into consideration, depending on their location.…”
Section: Enhancement Of the Distribution Grid And Development Of A Lo...mentioning
confidence: 99%